Chronicling Poverty
XI, 248 p.
Keywords: Over the last twenty years more and more historians of the eighteenth and early nineteenth centuries have turned their eyes away from the records of central administration, towards local archives, and the lives of the poor. What they have found is a wealth of sources some of which chronicle the lives, and many of which record the words, of working people. This book will bring together some of the best work based on these sources.